87.2k views
4 votes
Solve the equation 4(x-2)=3x+1

User Niksmac
by
4.9k points

2 Answers

4 votes

Answer:

Step-by-step explanation: x=9

User MikeyBeLike
by
5.4k points
5 votes

4(x-2)=3x+1

Mutiply the first bracket by 4

(4)(x)(4)(-2)= 3x+1

4x-8= 3x+1

Move 3x to the other side.

Sign changes from +3x to -3x.

4x-3x-8= 3x-3x+1

4x-3x-8= 1

x-8= 1

Move -8 to the other side.

Sign changes from -8 to +8.

x-8+8= 1-8

x= 9

Answer: x= 9

User Markhogue
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.